Effect of Acetic Acid and Sodium Benzoate on Growth of Penicillium expansum and Patulin Production - Sumaiya N. Hawar; Batool Z. Ali; Hifaa A. Yousif (Journal of Madenat Alelem University College, 2015)
The study was conducted to evaluate the effect of two food preservatives acetic acid and sodium benzoate on growth of Penicillium expansum and patulin production. Results showed complete inhibition of growth at conc. 0.5 and 1% while 0.1% showed reduction of growth equal to 75% +and patulin reduction of 84.33%. whereas, treatment of the fungus with different concentrations of sodium benzoate showed complete inhibition of growth at conc. 0.03%, lower concentrations 0.0003 and 0.003% revealed reduction of growth arrived to 58 and 82% respectively and reduction of 48.97% patulin production at conc. 0.0003%, and no patulin was detected at conc. 0.003%.